Cognitive complaints mediate the influence of sleep disturbance and state anxiety on subjective well-being and ill-being in adult community volunteers: a cross sectional study - Kuniyoshi Toyoshima; Masahiko Ichiki; Takeshi Inoue; Akiyoshi Shimura; Jiro Masuya; Yota Fujimura; Shinji Higashi; Ichiro Kusumi (BMC, 2022)
Abstract Background Sleep disturbance, state anxiety, and cognitive complaints (CCs) have been recognized as important issues in public health. Although the mediating role of CCs has been proposed, their role in the relationships between sleep disturbance, state anxiety, and subjective well-being (SWB) and subjective ill-being (SIB) are not yet fully understood. This study used path analyses to investigate whether CCs mediate these relationships. Methods The study recruited 523 Japanese adult volunteers using convenience sampling. Participants completed the Pittsburgh Sleep Quality Index, State-Trait Anxiety Inventory (Form Y), Cognitive Complaints in Bipolar Disorder Rating Assessment, and Subjective Well-Being Inventory to evaluate sleep disturbance, state anxiety, CCs, and SWB and SIB, respectively. Path analyses were conducted to assess the mediating effects of CCs. Results The path analyses showed significant indirect associations of sleep disturbance and state anxiety with SWB (p = 0.024 and p = 0.012) and SIB (p < 0.001 and p < 0.001), respectively, mediated by CCs. Furthermore, there were significant indirect associations of sleep disturbance with CCs (p < 0.001), SWB (p < 0.001), and SIB (p < 0.001), via state anxiety, respectively. Conclusions This study suggests that CCs mediate the associations of sleep disturbance and state anxiety with SWB and SIB, respectively, in adult community volunteers. To address SWB and SIB associated with sleep disturbance and state anxiety, evaluating CCs may be useful in public mental health. Our findings will encourage health care workers to assess CCs more systematically. Future studies may need to target CCs to develop interventions for SWB and SIB.